O curso de Pedagogia na Universidade Federal de Mato Grosso - campus Cuiabá (anos 1960-70) : uma análise histórica - Cunha, Ana Karolina dos Santos e (2024)
This research is part of the field of education and historical studies. The object of this study is the history of the Pedagogy course in Cuiabá, Mato Grosso, from the 1960s to the 1970s. The years 1960 to 1970 are the time frame, since the Pedagogy course was offered at the Science and Arts Institute of Cuiabá, beginning its academic year in the 1960s and ending in 1970, when the Federal University of Mato Grosso (UFMT) was created, integrating the Institute with other colleges in Cuiabá by Law No. 5,647, December 10 1970. The research question is: how did the Pedagogy course at the Federal University of Mato Grosso - Cuiabá Campus - contribute to the training of education professionals during the 1960s and 1970s? Considering the aforementioned spatial and temporal delimitation, the specific objectives were: to analyze the historical and educational context that gave rise to the Pedagogy course at UFMT; to identify the main milestones that occurred in the Pedagogy course at UFMT; to investigate the training offered by the Pedagogy course at UFMT. The methodology used was bibliographical and documentary research. The sources for the research were: political pedagogical projects; institutional documents; legislation; regulations; decrees; newspapers; iconography; norms; among other academic documents. This documentation was collected from different archives, such as: the Mato Grosso Public Archives, the Legislative Instituto Memória, the State Education Department, the State Education Council, the Cuiabá Extinct Schools Archives Center, the UFMT Rectory Archives, the UFMT School Administration Coordination Archives, the UFMT's Education Institute Centro de Memória Viva, Center and other institutional archives. In the end, we believe that the Pedagogy course played a crucial role in training teachers for primary education and other qualifications, as well as for the functions of educational supervision and administration. This process of integration not only expanded the range of courses on offer, but also made it possible for teaching, research and extension to be more closely linked, strengthening the training of educators and researchers in the region.